2019
DOI: 10.1111/tid.13101
|View full text |Cite
|
Sign up to set email alerts
|

Severe hemorrhagic cystitis caused by the BK polyomavirus is associated with decreased survival post‐allogeneic hematopoietic stem cell transplantation

Abstract: Background: BK polyomavirus reactivation can occur following allogeneic hematopoietic stem cell transplantation (allo-HSCT) and may lead to hemorrhagic cystitis (BKPyV-HC). We hypothesized that development of BKPyV-HC is associated with increased mortality post allo-HSCT. Methods: We retrospectively reviewed data on 133 adult patients (≥18 years old) who underwent allo-HSCT from 2007 until 2014 at Hospital Israelita Albert Einstein in São Paulo, Brazil. Results: Thirty-six patients presented with BKPyV-HC afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 39 publications
6
27
1
2
Order By: Relevance
“…Lu et al [ 23 ] showed that the occurrence of HC during non- in vitro depletion of T cell haploids was significantly higher than that of homologous transplantation and believed that ATG was related to the occurrence of HC. Kerbauy et al [ 7 ] indicated that the use of ATG during pretreatment significantly increased the BKPyV infection-associated incidence of HC. A recent study by Mo et al [ 24 ] showed that the cumulative incidence of HC after haplo-HSCT in 149 cases of ATG-based MAC was 29.8% and the cumulative incidence of severe (Grades III–IV) HC was 10.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al [ 23 ] showed that the occurrence of HC during non- in vitro depletion of T cell haploids was significantly higher than that of homologous transplantation and believed that ATG was related to the occurrence of HC. Kerbauy et al [ 7 ] indicated that the use of ATG during pretreatment significantly increased the BKPyV infection-associated incidence of HC. A recent study by Mo et al [ 24 ] showed that the cumulative incidence of HC after haplo-HSCT in 149 cases of ATG-based MAC was 29.8% and the cumulative incidence of severe (Grades III–IV) HC was 10.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Kerbauy et al [ 7 ] reported that HC did not significantly affect long-term survival but severe HC would reduce the long-term survival after transplantation. However, it has been shown that BKV-associated HC is a main cause of morbidity after allo-HSCT and is associated with prolonged hospitalization [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The urethra is more narrow in younger patients, which is closely associated with the CBI failure of HC. Lucila et al [9]. reviewed 133 recipients undergoing HSCT and found that younger patients were more likely to develop BK polyomavirus related HC in multivariate regression analysis and had a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The urethra is more narrow in younger patients, which is closely associated with the CBI failure of HC. Lucila et al [11]. reviewed 133 recipients undergoing HSCT and found that younger patients were more likely to develop BK polyomavirus related HC in multivariate regression analysis and had a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%